Under construction – contemporary opera in the crossroads between new aesthetics, techniques, and technologies - Kallionpää, Maria; Chamberlain, Alan; Gasselseder, Hans-Peter (2018)
Despite of its long history, opera as an art form is constantly evolving. Composers have never lost their fascination about it and keep exploring with innovative aesthetics, techniques, and modes of expression. New technologies, such as Virtual Reality (VR), Robotics and Artificial Intelligence (AI) are steadily having an impact upon the world of opera. The evolving use of performance-based software such as Ableton Live and Max/MSP has created new and exciting compositional techniques that intertwine theatrical and musical performance. This paper presents some initial work on the development of an opera using such technologies that is being composed by Kallionpää and Chamberlain. Furthermore, it presents two composition case studies by Kallionpää: “She” (2017) and puppet opera “Croak” (2018), as well as their documentation within the world's first 360° 3D VR recordings with full spatial audio in third-order Ambisonics and the application of an unmixing paradigm for focusing and isolating individual voices.